The Effectiveness of Play Therapy in Hospitalized Children with Cancer: Systematic Review - Ibrahim, Hajaratul Azwaningsih; Arbianingsih; Amal, Andi Adriana; Huriati (Journal Of Nursing Practice, 2020)
Background: Play therapy in cancer children is a major intervention that can meet the needs of playing in children who are hospitalized.Purpose: This study aimed to determine an effective play therapy model given to children with cancer undergoing hospitalization.Methods: The research design used is quantitative descriptive with a Systematic Review approach. Data collection techniques using article search sources in this study are Pubmed, Science Direct, Google Schoolar, Portal Garuda, JOIN, IJSR, and Emerald. Articles published from 2015-2019 and focus on play therapy interventions in children suffering from cancer.Results: The results of the analysis of nine articles in accordance with the inclusion criteria about play therapy in children with cancer proved effective in reducing hospitalization of children. The play therapy used in the selected article is drawing, painting, puzzle, storytelling, cognitive behavior and therapeutic play with 20-60 minutes of execution time.Conclusion: The play therapy is recommended for use because the technique is simple, does not require a lot of tools and materials, is easy, affordable and can be done by children with preschool and school-age cancer who are hospitalized.